Evaluation of Business Strategy and Performance in Chemical Companies with Micro Business category Case : Isnen Lab - Cheryl Marlitta Stefia (Ridwan Institute, 2022)
Micro, small, and medium-sized industries are one of the pillars of the Indonesian economy. Evidently during the pandemic, Indonesia can survive the threat of recession in 2020 not spared from the contribution of the domestic consumption sector, by also utilizing the circular economy. Although the turnover of industries engaged in services is declining, pandemic periods can be used by companies to increase human resource capacity. In the future when the economy improves, The company is ready to compete healthily in the market. Common problems faced by industries with micro, small, and medium scale are limited human resource capacity and incomprehension to the basics of business. This can be inferred from the stagnant performance of micro businesses. This study was conducted on isnen Laboraorium. The purpose of this study is to improve business efficiency performance. At the end of the research period, it is expected that there will be an overhaul of the 4 pillars of the business so that Isnen Lab will develop optimally